Multivalent Smallpox DNA Vaccine Delivered by Intradermal Electroporation Drives Protective Immunity in Nonhuman Primates Against Lethal Monkeypox Challenge - Hirao, Lauren A. (Oxford University Press, 2011)
The threat of a smallpox-based bioterrorist event or a human monkeypox outbreak has heightened the importance of new, safe vaccine approaches for these pathogens to complement older poxviral vaccine platforms. As poxviruses are large, complex viruses, they present technological challenges for simple recombinant vaccine development where a multicomponent mixtures of vaccine antigens are likely important in protection. We report that a synthetic, multivalent, highly concentrated, DNA vaccine delivered by a minimally invasive, novel skin electroporation microarray can drive polyvalent immunity in macaques, and offers protection from a highly pathogenic monkeypox challenge. Such a diverse, high-titer antibody response produced against 8 different DNA-encoded antigens delivered simultaneously in microvolumes has not been previously described. These studies represent a significant improvement in the efficiency of the DNA vaccine platform, resulting in immune responses that mimic live viral infections, and would likely have relevance for vaccine design against complex human and animal pathogens.